Pengembangan Ekonomi Kreatif Berbasis Lingkungan Melalui Pelatihan Totebag Ecoprint bagi UMKKM Desa Baros - Mohammad Yudi Indriawan; Gelar Fajar Ramadhan; Livia Widiawati Amanda; Rakaterra Grisva Igtiberian; Rita Ananda (Jurnal Pengabdian Tri Bhakti, 2025)
Baros Village’s local microenterprises face challenges in innovating new creative products, limiting the growth of the community’s economy. This community service program introduces an environmentally friendly creative economy initiative through ecoprint tote bag training for local MSMEs. The training encompasses education on eco-printing techniques—which use natural plant materials to dye fabric without synthetic chemicals—as a sustainable alternative for product development. The method of implementation involved lectures, demonstrations, and hands-on practice in making ecoprint tote bags. Participants, consisting of local entrepreneurs and community members, learned each stage of the ecoprint process from fabric mordanting to leaf printing and steaming. Results show that the training successfully equipped participants with new skills in producing eco-friendly tote bags, as evidenced by their ability to create unique ecoprint products showcased at the Baros Ngahiji event. This showcase received positive feedback and indicated a market interest in the eco-printed products. The discussion highlights that introducing ecoprint has opened opportunities for local MSMEs to develop value-added products with wider market potential. The program contributes to empowering the community’s economy by fostering creativity and environmental awareness. In conclusion, the ecoprint tote bag training program in Baros Village effectively provided new capabilities and business ideas for local MSMEs, supporting sustainable creative economy development at the village level.